Microscopic approaches to quantum liquids in confined geometries - Krotscheck, Eckhard (World Scientific, 2002)
Includes bibliographical references and index.; Quantum liquids in confined geometries exhibit a large variety of new and interesting phenomena. For example, the internal structure of the liquid becomes more pronounced than in bulk liquids when the motion of the particles is restricted by an external matrix. Also, free quantum liquid droplets enable the study of the interaction of atoms and molecules with an external field without complications arising from interactions with container walls. This volume assembles review articles that present the status of frontline research in this field in a manner that makes the material accessible to the educated, but non-specialist, reader. The articles focus on the many-body aspects of the theory of quantum liquids in confined geometry. Research is in the very satisfactory situation where several accurate approaches are available that allow one to describe these systems in a quantitative manner without modelling uncertainty and uncontrolled assumptions. For example, dynamic situations of direct experimental relevance can be modelled with high accuracy.